Effects of predictable behavioral patterns on anxiety dynamics - Lang, Martin; Krátký, Jan; Xygalatas, Dimitris (Scientific reports, 2022)
People face stressors that are beyond their control and that maladaptively perpetuate anxiety. In these contexts, rituals emerge as a natural coping strategy helping decrease excessive anxiety. However, mechanisms facilitating these purported effects have rarely been studied. We hypothesized that repetitive and rigid ritual sequences help the human cognitive-behavioral system to return to low-entropy states and assuage anxiety. This study reports a pre-registered test of this hypothesis using a Czech student sample (n = 268). Participants were exposed to an anxiety induction and then randomly assigned to perform one of three actions: ritualized, control, and neutral (no-activity). We assessed the effects of this manipulation on cognitive and physiological anxiety, finding that ritualized action positively affected anxiety decrease, but this decrease was only slightly larger than in the other two conditions. Nevertheless, the between-condition differences in the reduction of physiological anxiety were well-estimated in participants more susceptible to anxiety induction.
Keywords: kompulzivní chování; úzkostné poruchy; rituální chování; Ceremonial Behavior; Compulsive Behavior; Humans; Anxiety Disorders; úzkost; Anxiety; lidé